Desenvolvimento de aplicações Web com base em modelagem 3D: módulo portal Web - Barbosa, Airton Estevão [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This paper presents the development of a Web application called CityFreedom based on 3D modeling. The developed system demonstrates the use of most revolutionary and innovative techniques to create Web portals with the integrated 3D navigation scenarios to their own pages, without requiring any kind of plug-ins or external software. Everything works on the basis of compatible browsers. The CtyFreedom aims to give the user the feeling of immersion in virtual reality so get to interact with a three-dimensional city in order to see new places, traveling in an area of town that has always thought of knowing or even analyze establishments long before attend-them. It's the freedom to know and traveling around the city in a simple and trivial way. It is a new trend, the future of Web systems development

Este trabalho apresenta o desenvolvimento de uma aplicação Web chamada CityFreedom baseada em modelagem 3D. O sistema desenvolvido demonstra a utilização das mais revolucionárias e inovadoras técnicas para criação de portais Web junto à navegação por cenários 3D integradas às próprias páginas, sem que seja necessária utilização de plug-ins ou softwares externos. Tudo funciona com base nos navegadores compatíveis. O CityFreedom visa proporcionar ao usuário a sensação de imersão em realidade virtual de tal maneira a conseguir interagir com uma cidade tridimensional no intuito de conhecer novos lugares, viajar por uma região da cidade que sempre pensou em conhecer ou mesmo analisar estabelecimentos muito antes de frequentá-los. É a liberdade de conhecer e viajar pela cidade de maneira simples e trivial. É uma nova tendência, o futuro de desenvolvimento de aplicações Web
Keywords: Serviços da Web; Engenharia de software; Internet na educação; ActionScript (Linguagem de programação de computador); Imagem tridimensional; Web services